Influence of lung volume on the interaction between cardiac output and cerebrovascular regulation during extreme apnoea. Issue 10 (29th September 2017) - Stembridge, Mike; Hoiland, Ryan L.; Bain, Anthony R.; Barak, Otto F.; Drvis, Ivan; MacLeod, David B.; MacLeod, Douglas M.; Madden, Dennis; Batinic, Tonci; O'Donoghue, Peter; Shave, Rob; Dujic, Zeljko; et al.
Abstract : New Findings: What is the central question of this study? Does the reduction in cardiac output observed during extreme voluntary apnoea, secondary to high lung volume, result in a reduction in cerebral blood flow, perfusion pressure and oxygen delivery in a group of elite free divers? What is the main finding and its importance? High lung volumes reduce cardiac output and ventricular filling during extreme apnoea, but changes in cerebral blood flow are observed only transiently during the early stages of apnoea. This reveals that whilst cardiac output is important in regulating cerebral haemodynamics, the role of mean arterial pressure in restoring cerebral perfusion pressure is of greater significance to the regulation of cerebral blood flow. We investigated the role of lung volume‐induced changes in cardiac output ( Q ̇ ) on cerebrovascular regulation during prolonged apnoea. Fifteen elite apnoea divers (one female; 185 ± 7 cm, 82 ± 12 kg, 29 ± 7 years old) attended the laboratory on two separate occasions and completed maximal breath‐holds at total lung capacity (TLC) and functional residual capacity (FRC) to elicit disparate cardiovascular responses. Mean arterial pressure (MAP), internal jugular venous pressure and arterial blood gases were measured via cannulation. Global cerebral blood flow was quantified by ultrasound and cardiac output was quantified by via photoplethysmography. At FRC, stroke volume and Q ̇ did not change from baseline ( P > 0.05). In contrast, during the TLC trial stroke volume and Q ̇ were decreased until 80 and 40% of apnoea, respectively ( P < 0.05). During the TLC trial, global cerebral blood flow was significantly lower at 20%, but subsequently increased so that cerebral oxygen delivery was comparable to that during the FRC trial. Internal jugular venous pressure was significantly higher throughout the TLC trial in comparison to FRC. The MAP increased progressively in both trials but to a greater extent at TLC, resulting in a comparable cerebral perfusion pressure between trials by the end of apnoea. In summary, although lung volume has a profound effect on Q ̇ during prolonged breath‐holding, these changes do not translate to the cerebrovasculature owing to the greater sensitivity of cerebral blood flow to arterial blood gases and MAP; regulatory mechanisms that facilitate the maintenance of cerebral oxygen delivery. Abstract :